RELIGION NARRATIVE IN THE FILM "HATI SUHITA" - Rodiyah, Nuning (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study examines the representation of religious narratives in the film Hati Suhita. The research aims to analyze how religious values are conveyed through cinematic elements, including dialogue, scenes, and visual aspects such as setting, symbols, and costumes. Method: A qualitative approach was employed using Norman Fairclough’s Critical Discourse Analysis. This method enables an in-depth examination of how religious narratives are structured and communicated within the film. The study focuses on three core aspects of Islamic teachings: Aqidah (faith), Syariah (Islamic law), and Akhlak (morality). Results: The findings indicate that religious narratives are presented through key Islamic teachings. Aqidah is depicted by emphasizing faith in the Almighty and the concept of divine destiny. Syariah is conveyed through dialogues and expressions that illustrate religious practices and their proper implementation within an Islamic framework. Akhlak is integrated holistically, incorporating both religious doctrine and universal humanistic values, which shape the overall moral message of Hati Suhita. Novelty: This study highlights the multifaceted representation of Islamic teachings in contemporary Indonesian cinema. By analyzing Hati Suhita through the lens of Critical Discourse Analysis, the research provides fresh insights into how religious values are interwoven into film narratives, not only as theological constructs but also as cultural and social influences within a modern cinematic context.